(3GdOQ GdedJbW ef cd HMQ hSbWs - (3eMeO Hf Ydj Hf eMehO GdcGJH, GdcGJH,J (B753 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3jbhd abjQ QMeg QHg GdbOjQ deG QCjJ QGFO dge hbO baHd, hfLe GdTHjHI bO ZQH hCad, ESJNQJ Gddg JYGdi aGdJbWJ ef GdOQ faGFSgG s
(3BNQgG (B:s
(3eQrJ jhekG HGdhRjQ Hf YHOhS, hgh LGdS CeGe HQcI JJhdO ef eGA GdCeWGQ ahbaJ CeGeg hJeKdJ HHjJ CHj fhGS aJQcJg dG jMjQ LhGHkG hdG jgJOj UhGHkG s
(3GdfSNI HgG MhGTs
(3HGdeYgO GdLRA GdKGfj hjMJhj Ydi GdHGH GdKGef Edi GdHGH GdNGeS YTQs
(3hHgGeTg JYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs